DETERMINATION OF POLYCYCLIC AROMATIC HYDROCARBONS AND VOLATILE ORGANIC COMPOUNDS IN SURFACE SOILS OF MECHANIC WORKSHOPS IN AZARE BAUCHI STATE, NIGERIA - Ahmed, Jibrima; Katagum, Yahaya Muhammed; Nuhu, Awwal Hussain; Abdulhameed, Adamu; Khalil, Buhari Ibrahim (FUDMA Journal of Sciences, 2025)
The study aimed was to determine the organic pollutants in mechanic workshop garages in Azare, Bauchi state, Nigeria. Soil samples were collected after two weeks in a month for three months, making two replicates from three (3) popular auto mechanic workshops using a hand auger. At each location, the surface soil samples was randomly collected from the same depth of 0 – 20 cm to form composite samples. Soil samples are dried to remove moisture, followed by sieving to remove debris the size of the mesh used 2 mm. the soil sample are typically oven dried at 105 oC for a period usually 16-24 hours. The GC-MS concentration of benzene, toluene, ethyl benzene, m,p xylene and o-xylene in site 1, was found to be 12.1±0.31, 9.5±0.02, 8.2±0.02, 7.5±0.01, 6.9±0.01, respectively. Which all are above WHO permissible limits that ranging from 0.01-0.20. Where the mean values of naphthalene, phenanthrene, Anthracene, fluoranthene, and pyrene in site 2, was found to be 6.2±0.01, 5.1±0.01, 5.5±0.01, 4.1±0.1and 3.9±0.01 respectively. Which all are above USEPA limits that ranging from 0.01-0.100. Where the mean values of decane, undecane, dodecane, tridecane, pentadecane in site 3, was found to be 21.9±2.00, 18.5±1.59, 15.2±1.50, 12.9±1.20, 10.5±1.00, respectively which all are above WHO permissible limit that ranging from 0.02-0.07. The GC-MS analysis of three different soil samples from the mechanic garages contained various organic pollutants, including VOCs, PAHs, and aliphatic hydrocarbons. The results highlight the need for proper waste disposal that become crucial for protecting both human health...
Keywords: Mechanic workshops; PAHs poly cyclic aromatic hydrocarbons; PCBs poly chlorinated biphenyls; SVOCs Semi volatile organic compound; Pollutants; Garages; Workshops